Back to sleep: Teaching adults to arrange safe infant sleep environments. Issue 3 (29th January 2020) - Carrow, Jacqueline N.; Vladescu, Jason C.; Reeve, Sharon A.; Kisamore, April N.
Abstract : There are over 3, 000 sleep related infant deaths each year in the United States. Attempts to teach medical personnel and parents safe infant sleep practices in the infant sleep training literature have demonstrated mixed results. Thus, strategies to teach arrangements of safe infant sleep environments warrant further investigation. Behavioral skills training (BST) is an evidence‐based teaching strategy shown to successfully teach various safety skills to children and adults. The current study evaluated the effectiveness of behavioral skills training to teach safe infant sleep practices to typically developing adults. Specifically, differential responding was assessed across multiple environmental arrangements typical of contexts parents may be exposed to when putting an infant to sleep. BST significantly improved appropriate arrangement of a safe sleep environment for infants for all 8 participants.